1997
DOI: 10.1002/hep.510260224
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of S-adenosylmethionine synthetase isozymes in different cell types of rat liver

Abstract: methylation reactions in vivo and also serves the propylMammalian S-adenosylmethionine (AdoMet) synthetase examino donor in polyamine biosynthesis. AdoMet synthetase ists as two isozymes, liver-type and nonhepatic-type enzymes, exists as two isozymes, liver-type and nonhepatic-type enwhich are the products of two different genes. It is known that zymes, respectively. The liver-type isozyme is confined to the liver-type isozyme is only expressed in adult liver. Whereas, the liver, whereas the nonhepatic-type is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 21 publications
1
27
0
Order By: Relevance
“…We and others have shown that the activity of the MATII enzyme composed of MATα2 and MATβ subunits is decreased during HSC activation despite an induction of MAT genes (Shimizu-Saito et al, 1997; Ramani et al, 2010) leading to a drop in SAMe levels and global DNA hypomethylation (Ramani et al, 2010) promoting HSC activation. Our mutation analysis shows that whereas the MATα2-P1 and P2 mutants (Table 1) do exhibit reduced binding to MATβ, they still promote HSC activation.…”
Section: Discussionmentioning
confidence: 92%
“…We and others have shown that the activity of the MATII enzyme composed of MATα2 and MATβ subunits is decreased during HSC activation despite an induction of MAT genes (Shimizu-Saito et al, 1997; Ramani et al, 2010) leading to a drop in SAMe levels and global DNA hypomethylation (Ramani et al, 2010) promoting HSC activation. Our mutation analysis shows that whereas the MATα2-P1 and P2 mutants (Table 1) do exhibit reduced binding to MATβ, they still promote HSC activation.…”
Section: Discussionmentioning
confidence: 92%
“…Metabolites of AdoMet, such as SAH and MTA, and methionine, a precursor of AdoMet, were used at 30 M and found to decrease collagen I protein and COL1A1 and COL1A2 mRNA levels in HSC (Fig. 4, C and D); however, the effects mediated by methionine were lower compared with those of the other treatments perhaps because of the extremely low expression of methionine adenosyltransferase 1A in HSC (36).…”
Section: Induction Of Liver Fibrosis In Mouse Col1a2 Promoter Transgementioning
confidence: 98%
“…Furthermore, two metabolites of AdoMet, SAH and MTA, were able to replicate these same effects at the protein and mRNA level. Methionine, an AdoMet precursor, also lowered collagen I protein and mRNA although less effectively, probably because of the minimal methionine adenosyltransferase 1A activity in HSC (36). Because SAH and MTA, unlike AdoMet, are not methylating agents, unless they generate AdoMet again, it is likely that the down-regulation of collagen I protein and mRNA by AdoMet may not be the result of gene silencing via methylation.…”
Section: Induction Of Liver Fibrosis In Mouse Col1a2 Promoter Transgementioning
confidence: 99%
“…We reported previously that in the kidney, MAT II was mainly localized in the distal tubules 17 and in the liver, MAT II was only expressed in the hepatic stellate cells. 18 The T/N ratio in the colon of our patient 3 was very high. This patient was diagnosed as having a villous tumor which is known to have high secreting activity.…”
Section: Discussionmentioning
confidence: 92%